pt <=> \(\sqrt{2x+1}-\sqrt{x+3}=\sqrt{x-1}-\sqrt{2x-1}\)
=> \(3x+4-2\sqrt{\left(2x+1\right)\left(x+3\right)}=3x-2-2\sqrt{\left(x-1\right)\left(2x-1\right)}\)
=> \(3-\sqrt{\left(2x+1\right)\left(x+3\right)}=-\sqrt{\left(x-1\right)\left(2x-1\right)}\)
=> \(9+\left(2x+1\right)\left(x+3\right)-6\sqrt{\left(2x+1\right)\left(x+3\right)}=\left(x-1\right)\left(2x-1\right)\)
<=> \(2x^2+7x+12-6\sqrt{\left(x+3\right)\left(2x+1\right)}=2x^2-3x+1\)
<=> \(10x+11=6\sqrt{\left(x+3\right)\left(2x+1\right)}\)
=> \(\left(10x+11\right)^2=36\left(x+3\right)\left(2x+1\right)\)
<=> \(100x^2+220x+121=36\left(2x^2+7x+3\right)\)
<=> \(28x^2-32x+13=0\)
<=> \(196x^2-224x+91=0\)
<=> \(\left(14x-8\right)^2+27=0\) (*)
Có: \(\left(14x-8\right)^2+27\ge27>0\)
=> PT (*) VÔ NGHIỆM.
VẬY PT \(\sqrt{2x+1}-\sqrt{x+3}=\sqrt{x-1}-\sqrt{2x-1}\) VÔ NGHIỆM.
đk x3
ta có
do cả hai vế lớn hơn nên cả bình phương cả 2 vế
pt<=> 2x+1=x+x-3+2<=> 2=
<=> 4=x^2-3x
<=>x^2-3x-4=0
<=> (x-4)(x+1)=0
<=> x=4(do x
Vậy S={4}